Aplicação do método de Ritz extendido na análise de vibrações e estabilidade dinâmica de placas circulares - Prato, Nivaldo (1973)
The aim of this paper is to present an appraximate soluction for the natural frequencies of circular plates, under axisynnetric transverse vibration. It was used the Ritz method to form a minimizing sequence for the energy functional. Initially a review of the basic principles of the variational calculus is presented. Then, the problem of axisylmmetric, transverse vibrations of a circular plate with torsional elastic support at its edge is solved. Finally, it is analyse:i the problem of a rotating circular plate with a central circular bole elastically supportedat its external edge.